The Blagodatnoe gold-sulfide deposit (Yenisei Ridge, Russia): the nature of geophysical anomalies and the succession and causes of formation of petrophysical zoning; Russian Geology and Geophysics; Vol. 55, iss. 11 - Kolmakov Yu. V. Yuriy Viktorovich (2014, 2014)
Title screen